2010
DOI: 10.1039/c0dt00416b
|View full text |Cite
|
Sign up to set email alerts
|

Calcium binding environments probed by 43Ca NMR spectroscopy

Abstract: Calcium is an important component of materials, metalloproteins, minerals, glasses, and small inorganic and organic complexes. However, NMR spectroscopy of the quadrupolar (43)Ca nuclide remains difficult primarily due to its low natural abundance and low resonance frequency. In this Perspective, experimental challenges and recent successes in the field are highlighted, with a focus on solid-state (43)Ca NMR spectroscopy. Solution (43)Ca NMR studies of calcium-binding biomolecules are also presented. The struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 52 publications
5
48
0
Order By: Relevance
“…Analytical line shape modeling of the static 43 Ca SSNMR spectrum allows us to report a calcium CS tensor span of 31 ± 5 ppm (Fig. 3a), which represents the fifth measurement of calcium CSA in the literature 73 and the first where oxygen atoms are not coordinated to the calcium. The calcium CS tensor span for CaCl 2 is moderate, as calcium CS tensor spans range Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Analytical line shape modeling of the static 43 Ca SSNMR spectrum allows us to report a calcium CS tensor span of 31 ± 5 ppm (Fig. 3a), which represents the fifth measurement of calcium CSA in the literature 73 and the first where oxygen atoms are not coordinated to the calcium. The calcium CS tensor span for CaCl 2 is moderate, as calcium CS tensor spans range Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…First 43 Ca NMR experiments started to appear from the late 90s, [12][13][14][15] and demonstrated the correlation between 43 Ca NMR parameters and Ca environment. However, 43 Ca solid state NMR is intrinsically difficult because 43 Ca is a quadrupolar nucleus (spin ¼7/2) with a very low natural abundance (0.135%) and a small gyromagnetic ratio (γ).…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, the NMR-active isotope, 43 Ca, is a spin-7/2 low-nucleus (i.e. with a small magnetic moment) of low natural abundance (< 0.14%), [38,83] which makes it particularly difficult to study by NMR. Nevertheless, we have recently shown that natural abundance 43 Ca solid state NMR is well adapted to the study of apatite phases.…”
Section: C Analysis Of the Local Environment Of The Calciummentioning
confidence: 99%